Country, climate change adaptation and colonisation: insights from an Indigenous adaptation planning process, Australia. Issue 3 (March 2018) - Nursey-Bray, Melissa; Palmer, Robert
Abstract: Indigenous peoples are going to be disproportionately affected by climate change. Developing tailored, place based, and culturally appropriate solutions will be necessary. Yet finding cultural and institutional 'fit' within and between competing values-based climate and environmental management governance regimes remains an ongoing challenge. This paper reports on a collaborative research project with the Arabana people of central Australia, that resulted in the production of the first Indigenous community-based climate change adaptation strategy in Australia. We aimed to try and understand what conditions are needed to support Indigenous driven adaptation initiatives, if there are any cultural differences that need accounting for and how, once developed they be integrated into existing governance arrangements. Our analysis found that climate change adaptation is based on the centrality of the connection to 'country' (traditional land), it needs to be aligned with cultural values, and focus on the building of adaptive capacity. We find that the development of climate change adaptation initiatives cannot be divorced from the historical context of how the Arabana experienced and collectively remember colonisation. We argue that in developing culturally responsive climate governance for and with Indigenous peoples, that that the history of colonisation and the ongoing dominance of entrenched Western governance regimes needs acknowledging and redressing into contemporary environmental/climate management.